Pemanfaatan Powerpoint Interaktif sebagai Media Pembelajaran dalam Meningkatkan Partisipasi Aktif Siswa pada Mata Pelajaran Pancasila Materi Bhineka Tinggal Ika (Penelitian Deskriptif Kelas X Multimedia SMK PGRI 3 Kota Serang) - E. Nita Prianti; Wiwin Winda Kusumawati (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This study examines the utilization of interactive PowerPoint as a learning media to enhance students' active participation in Pancasila subjects, specifically the material of Bhineka Tunggal Ika, using a descriptive qualitative research method. The primary objective of this study is to understand how interactive PowerPoint can be implemented in the learning process and how its use affects students' involvement in the classroom. The research was conducted at SMK PGRI 3 Kota Serang involving 43 tenth-grade multimedia students and one Pancasila teacher as participants. Data was collected through in-depth interviews with teachers and students, observations during the learning process, and analysis of documentation related to the implementation of interactive PowerPoint. Observations were conducted to assess classroom dynamics, student participation levels, and interactions that occurred during learning sessions. The results of the analysis indicate that the use of interactive PowerPoint significantly increased student involvement in learning. Students showed greater interest and actively participated in discussions and activities presented through PowerPoint. Teachers also reported that the material delivered with the help of interactive PowerPoint was easier to understand and more interesting for students. Several PowerPoint features, such as interactive quizzes and animations, proved effective in facilitating the understanding of the concept of Bhineka Tunggal Ika. This study concludes that interactive PowerPoint is an effective tool for enhancing students' active participation in Pancasila learning. The use of this media not only increases student involvement but also assists teachers in delivering material in a more engaging and interactive manner. These findings provide valuable insights into the integration of technology in education and offer recommendations for the development of more innovative learning methods.